Adopting Mobility-as-a-Service: An empirical analysis of end-users' experiences. (July 2022) - Smith, Göran; Sochor, Jana; Karlsson, I.C. MariAnne
Highlights: Provides empirical evidence on end-users' perspective on, and use of, MaaS. Identifies drivers and barriers to the adoption of MaaS. Illustrates that MaaS is much more than just an app and a subscription plan. Highlights a mutually reinforcing relationship between MaaS and policies aimed at reducing car use. Abstract: Despite widespread interest, empirical research on how end-users perceive and use Mobility-as-a-Service (MaaS) is scarce. To address this knowledge gap, this article analyzes the end-user process of adopting a MaaS service entitled EC2B, which was launched in Gothenburg, Sweden, in the spring of 2019. The contribution to the MaaS literature is three-fold. Firstly, the article provides insight into potential end-users by describing the characteristics and motives of the studied group of adopters. Secondly, it improves the understanding of the potential effects of MaaS by outlining how the EC2B service was used and how it influenced travel behavior. Thirdly, the article informs strategies for facilitating MaaS adoption by outlining what types of drivers and barriers the end-users faced during different stages of the adoption process. The reported findings underscore previous assertions that MaaS is much more than just an app and a subscription plan and highlight a mutually reinforcing relationship between the introduction of MaaS and the implementation of policies aimed at reducing car use.